Models of dust and gas tori in active galactic nuclei - Schartmann, Marc (2007)
The goal of this thesis is to gain theoretical understanding of the distribution of dust and gas in the innermost parsecs of Active Galactic Nuclei. Unified schemes demand a circum-nuclear disk or "torus" to geometrically unify two separate classes of observed objects (face-on and edge-on view onto the torus). In a multi-step approach, we work towards the establishment of realistic simulations of this massive and dense gas and dust reservoir, in order to be able to interpret near- and mid-infrared interferometric observations (MIDI, AMBER), which are able to resolve dust structures in the centres of Seyfert galaxies. In a first step, we investigate an analytical torus model (the so-called "Turbulent Torus Model") with the help of radiative transfer calculations and find gross agreement with large aperture, as well as high-resolution observations of Seyfert galaxies. However, the model SEDs show too pronounced silicate emission features in the face-on case. This can be overcome with the help of three-dimensional clumpy tori, calculated in a second step. Special emphasis is put on the differences of clumpy and continuous dust distributions, also concerning interferometric observations. In a further step, we apply hydrodynamic simulations to trace the evolution of a nuclear star cluster, which provides energy via discrete supernova explosions and mass from stellar mass loss...
Keywords: Hochschulschrift; Numerisches Modell; Torus; Interstellares Gas; Interstellarer Staub; Aktiver galaktischer Kern